Effects of a kefir supplement on symptoms, colonic transit, and bowel satisfaction score in patients with chronic constipation: A pilot study - Turan, İlker and Dedeli, Özden and Bor, Serhat and İlter, Tankut (Turkish Journal of Gastroenterology, 2014)
Abstract Background/Aims: Although probiotics have been extensively studied in irritable bowel syndrome, data on the impact of probiotics on chronic constipation are scarce. We aimed to evaluate the effects of kefir, which is a probiotic fermented milk product, on the symptoms, colonic transit, and bowel satisfaction scores of patients with chronic constipation. Materials and Methods: Twenty consecutive patients with functional constipation according to the Rome II criteria were divided into two groups based on their colon transit studies: 1. The normal transit (NT) group (n=10); and 2. The slow transit (ST) group (n=10). After a baseline period, 500 mL/day of a probiotic kefir beverage was administered to all patients for 4 weeks. Defecation parameters (stool frequency, stool consistency, degree of straining, laxative consumption) were recorded in diaries daily by the patients. Bowel satisfaction scores were assessed using a visual analog scale. The colon transit study was repeated in the ST group at the end of the study. Results: At the end of the study, the patients showed an increased stool frequency (p<0.001), improved stool consistency (p=0.014), and decreased laxative consumption (p=0.031). The degree of straining during evacuation showed a tendency to improve after kefir administration; however, this was not statistically significant (p=0.18). A repeat transit study showed an acceleration of colonic transit in the ST group (p=0.013). Bowel satisfaction scores also improved (p<0.001). Conclusion: This pilot study shows that kefir has positive effects on the symptoms of constipation. Our results also suggest that kefir improves bowel satisfaction scores and accelerates colonic transit. Controlled trials are warranted to confirm these findings.